Analysis of the Implementation of the Occupational Safety and Health Management System (SMK3) at the Initial Level at PT X and Y - Alfina, Nadya Aulia; Wahyuningsih, Anik Setyo (Jurnal Kesmas Prima Indonesia, 2025)
Occupational safety and health contain the value of protecting workers from accidents or occupational diseases. The garment industry is generally a safe workplace compared to other sectors. The primary health risks come from minor but ongoing hazards whose effects persist over time and can potentially cause work accidents or occupational diseases. This study aimed to describe the implementation of the Occupational Safety and Health Management System (SMK3) at the initial level in the garment industry in Central Java. The type and design of the study used a quantitative descriptive method with a purposive sampling method. Data collection methods were interviews, observations, and documentation studies. The instrument used was a questionnaire on implementing the Occupational Safety and Health Management System (SMK3) at the initial level based on PP No. 50 of 2012 belonging to the Central Java Provincial Occupational Safety Center. The validity test of the data used source triangulation and technique triangulation techniques, and then the data was analyzed using univariate analysis. The study results showed that the implementation of the SMK3 at the initial level in international companies was more comprehensive compared to national companies that needed improvements to increase the level of SMK3 implementation. The initial level of SMK3 implementation in international garment companies is 93.6%, which is a satisfactory category, while in national companies, it is 70.9%, which is a good category. Kata kunci: Penerapan; SMK3; Industri Garmen